Incidence of reproductive disorders in the stray dogs in Dehradun district of Uttaranchal - KUMAR, SARVESH; SHARMA, V K; SINGH, BEERENDRA (The Indian Journal of Animal Reproduction, 2007)
The study was conducted on 918 stray dogs in Dehradun brought for sterilization, 38 (4.14%) dogs were suffering with pathological conditions. The pathological conditions most encountered were venereal tumor, 2.28% (2.36% female and 2.0% male) respectively, mammary tumor ( 1.11 % ), pyometra (0.97%) and unilateral cryptorchidism (1.0%).